Authority and Knowledge in Islamic Intellectual Tradition: A Critical Inquiry into Epistemic Legitimacy in the Age of Information Overload - Syarifudin Syarifudin; Aan Kudrotulloh; Ade Imun Romadan (International Forum of Researchers and Lecturers, 2025)
The digital age has brought significant transformations to various sectors, including religious scholarship, where traditional structures of authority are being challenged by the rise of digital media and influencers. This study explores the implications of digital disruption in the Islamic context, focusing on how digital platforms are reshaping authority and epistemic legitimacy. In particular, the emergence of